Exogenous hemin improves Cd2+ tolerance and remediation potential in Vigna radiata by intensifying the HO-1 mediated antioxidant defence system - Lovely Mahawar (Nature Portfolio, 2021)
Abstract The present study evaluated the effects of exogenous hemin on cadmium toxicity in terms of metal accretion and stress resilience in Vigna radiata L. (Wilczek). One-week-old seedlings were treated with CdCl2 (50 μM) alone and in combination with hemin (0.5 mM) in half-strength Hoagland medium for 96 h. The optimum concentrations of Cd and hemin were determined on the basis of haem oxygenase-1 activity. The results demonstrated that under Cd stress, plants accumulated a considerable amount of metal in their tissues, and the accumulation was higher in roots than in leaves, which significantly reduced the plant biomass and chlorophyll content by increasing the oxidative stress (MDA and H2O2 content). However, hemin supplementation under Cd,-stress improved plant growth by enhancing the harvestable biomass and photosynthetic pigments, increasing antioxidant activities (SOD, APX, POD, HO-1 and proline), lowering oxidative damage and increasing Cd tolerance in plants. Furthermore, the application of hemin enhances the removal efficiency of Cd in V. radiata by increasing the uptake of Cd via roots and its translocation from roots to foliar tissues. Thus, the study suggests that hemin has the potential to improve the stress tolerance and phytoremediation ability of heavy metal-tolerant plants so that they can be used instead of hyperaccumulators for remediation of Cd-contaminated environments.